Improving Learning Activity Through the Application of the Picture and Picture Model in Education Citizenship in School Base - Hanum, Latifa (International Journal of Students Education, 2024)
Picture and Picture learning model in civic education in elementary schools has been proven effective in increasing student learning activity. This study focuses on students in several elementary schools who experience low learning outcomes in Civic Education subjects. Through the research method used by the author, namely literature review, is data literature outlined And interpreted with scientific explanation. then the author explores and reviews several journals, books, websites. With see articles which spread in google, google researcher, and research gate using selected keywords, then draw conclusions and also summarize so that it can answer the article that the author made. This study aims to increase motivation and improve student learning in the teaching and learning process using the picture and picture learning model. The results of the study showed that student learning activity was on category currently. However, with implementation model Picture and Picture, where students are invited to match relevant pictures with the teaching material, the results show a significant increase after implementing this model. The results show that student activity increases to a high category, reflecting their greater interest and attention to the material being taught. This learning model provides a more enjoyable learning experience and interactive for student with use picture as learning media. This is very important in citizenship education, in where understanding values nationality and right as well as obligation as Citizenship needs to be instilled in elementary school students.